POLA BAHASA DALAM DOANGANG: PELESTARIAN PUISI MAKASSAR MELALUI KAJIAN MEMORI SASTRA - Nur Hasbi; Asis Nojeng; Sahban Nur (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the language patterns in doangang that reflect the literary memory of the Makassar people. The method used is a qualitative method with a literary memory approach. The research data source is the doangang text Aklampa Akboya Dallek which is analyzed using data collection techniques through documentation studies and reading and note-taking techniques. Data analysis is carried out using interactive methods that include data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the language patterns in doangang are formed due to three main elements, namely fixed formulas, relational metaphors, and language refinements. Fixed formulas act as mnemonic devices that maintain the continuity of texts in oral literature. Relational metaphors describe the symbolic relationship between humans, God, the Prophet, and the cosmological direction when seeking sustenance. Language refinements function as a way to aestheticize literary memory through religious and polite expressions. This study emphasizes that doangang is not merely oral poetry, but also functions as a means to store and pass on the cultural memory of the Makassar people.